Research impact of digital culture on digital transformation in Vietnam businesses - Anh, Nguyen Lan; Tran, Thi Thu Ha (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2022)
Objective: Digital transformation is a process that has an impact on all sectors of society, especially on the economy, economy and businesses. Digital transformation opens up new and limitless possibilities for business operations. However, an organization that wants to accelerate digital transformation needs to first focus on its people-or its culture. Digital transformation is not only about technology, but the key issue is transforming the values, beliefs and goals of the business first. Businesses are one of the organizations that are experiencing the rapid and powerful impact of digital transformation in many fields. Method: this study focuses on understanding the influence of digital cultural factors on the digital transformation process in Vietnamese enterprises, using the framework of 7 digital cultural factors (feasibility, openness, knowledge, reliability, agility, interdependence and accountability) by Cigref research. The study has collected 305 survey questionnaires by means of an online Google form survey and sent to business members operating in Vietnam at random. Conclusion: The survey data is processed by SPSS 16 software to find out the influence of each factor through the standardized regression model of the research variables.